1989
DOI: 10.1037/1040-3590.1.4.266
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Neuropsychology Behavior and Affect Profile.

Abstract: This series of 4 studies describes the psychometric properties of the Neuropsychology Behavior and Affect Profile, which consists of 5 peer-rated scales (106 items) designed to measure personality change in brain-impaired individuals. Study 1 pertains to item derivation. Study 2 used relatives of 61 Ss identified as demented to determine the test's internal consistency. Results showed moderate levels of internal consistency across the 5 scales, with slightly higher coefficients (.6S-.82) obtained for present (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 28 publications
3
50
0
1
Order By: Relevance
“…Measures of post-TBI Bbehavior changes^(e.g., Head Injury Behaviour Scale, Godfrey et al, 2003;Overt Behaviour Scale, Todd, Kelly, & Simpson, 2002;Neurobehavioral Functioning Inventory, Kreutzer, Seel, & Marwitz, 1999;Neurobehavioral Symptom Inventory, Cicerone & Kalmar, 1995) assess characteristics often also referred to as personality disturbances (e.g., aggressiveness, depression, irritability, social inappropriateness, childishness, and impulsivity). Measures that assess personality changes related to dementia (e.g., Neuropsychology Behavior and Affect Profile, Nelson et al, 1989;Revised Memory and Behavior Problems Checklist, Teri, Truax, & Logsdon, 1992) and general personality (e.g., NEO Personality InventoryRevised [NEO PI-R], Costa & McCrae, 1992;Eysenck Personality Questionnaire-Revised, Eysenck & Eysenck, 1991) overlap with post-TBI personality disturbance descriptions (e.g., the Neuropsychology Behavior and Affect Profile assesses depression, indifference, and inappropriateness, Cannon, 2000; the NEO PI-R assesses sociability, suspiciousness, depressiveness, anxiousness, angry hostility, and impulsiveness, Costa & McCrae, 1992) and have thus been used to assess individuals with TBI (e.g., Jackson, Turner-Stokes, Murray, & Leese, 2007;Kurtz, Putnam, & Stone, 1998;Malec, Brown, & Moessner, 2004;Rush, Malec, Brown, & Moessner, 2006;Tate, 2003).…”
Section: Assessment Of Post-tbi Personality Disturbancesmentioning
confidence: 99%
“…Measures of post-TBI Bbehavior changes^(e.g., Head Injury Behaviour Scale, Godfrey et al, 2003;Overt Behaviour Scale, Todd, Kelly, & Simpson, 2002;Neurobehavioral Functioning Inventory, Kreutzer, Seel, & Marwitz, 1999;Neurobehavioral Symptom Inventory, Cicerone & Kalmar, 1995) assess characteristics often also referred to as personality disturbances (e.g., aggressiveness, depression, irritability, social inappropriateness, childishness, and impulsivity). Measures that assess personality changes related to dementia (e.g., Neuropsychology Behavior and Affect Profile, Nelson et al, 1989;Revised Memory and Behavior Problems Checklist, Teri, Truax, & Logsdon, 1992) and general personality (e.g., NEO Personality InventoryRevised [NEO PI-R], Costa & McCrae, 1992;Eysenck Personality Questionnaire-Revised, Eysenck & Eysenck, 1991) overlap with post-TBI personality disturbance descriptions (e.g., the Neuropsychology Behavior and Affect Profile assesses depression, indifference, and inappropriateness, Cannon, 2000; the NEO PI-R assesses sociability, suspiciousness, depressiveness, anxiousness, angry hostility, and impulsiveness, Costa & McCrae, 1992) and have thus been used to assess individuals with TBI (e.g., Jackson, Turner-Stokes, Murray, & Leese, 2007;Kurtz, Putnam, & Stone, 1998;Malec, Brown, & Moessner, 2004;Rush, Malec, Brown, & Moessner, 2006;Tate, 2003).…”
Section: Assessment Of Post-tbi Personality Disturbancesmentioning
confidence: 99%
“…Un désordre neurologique induit des changements non seulement cognitifs, mais encore émotionnels. Nelson et al (1989) ont élaboré 106 items quantifiant les cinq domaines de patterns de changements comportementaux établis par Bear (1983) [2], que sont :…”
Section: Vitesse De Traitementunclassified
“…For example, Nelson et al [29] identified changes associated with ABI from the literature and then categorized them in terms of their impact on emotional function. They conceptualized five such factors: indifference (denial or reduced awareness); mania (impulsivity, irritability and euphoria); depression (including apathy and withdrawal); inappropriateness (unusual or bizarre behaviour); and pragnosia (impairment in the pragmatics of communicative style).…”
Section: Introductionmentioning
confidence: 99%
“…For example, attentional impairment may contribute towards both indifference and mania. The Nelson et al [29] approach also recognizes that the reason why characteristics of ABI fall within each category can vary between people. This way of conceptualizing ABI outcome, by seeking common overlap between various symptoms, is certainly far more useful to clinicians than that offered by broad categories of function, such as cognitive vs. noncognitive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation